2000
DOI: 10.1001/archinte.160.12.1810
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Omeprazole for the Treatment of Symptomatic Acid Reflux Disease Without Esophagitis

Abstract: Background: Up to three quarters of patients with gastroesophageal reflux disease (GERD) have symptoms, such as heartburn, but no macroscopic evidence of erosive esophagitis, making symptomatic GERD a common clinical problem in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 36 publications
2
97
1
1
Order By: Relevance
“…In this study in erosive GERD (endoscopy positive) patients resolution of heart burn occured more in patient taking IR-OMEP (75%) than in patient taking DR-OMEP. A clinical trial conducted by Ricter et al, showed that at the end of 4 weeks 76% of patients had complete resolution of heartburn with DR-OMEP 24 . Biswjit D has also shown resolution of heartburn by DR-OMEP is 76% patients 18 .…”
Section: Gerd (N=69)mentioning
confidence: 99%
“…In this study in erosive GERD (endoscopy positive) patients resolution of heart burn occured more in patient taking IR-OMEP (75%) than in patient taking DR-OMEP. A clinical trial conducted by Ricter et al, showed that at the end of 4 weeks 76% of patients had complete resolution of heartburn with DR-OMEP 24 . Biswjit D has also shown resolution of heartburn by DR-OMEP is 76% patients 18 .…”
Section: Gerd (N=69)mentioning
confidence: 99%
“…Richter et al [9] compared the efficacy of omeprazole 20 mg vs. omeprazole 10 mg vs. placebo. All efficacy data regarding heartburn were recorded in a patient diary.…”
Section: Examplesmentioning
confidence: 99%
“…The primary outcome measure in many clinical studies of reflux disease is the proportion of patients with total symptom relief [7, 8]. This outcome measure is methodologically attractive, but might be in conflict with what is considered clinically useful in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%